HIV/AIDS Estimation and Projection in Thailand.Experience During 1989 - 1993 - Thanprasertsuk, Sombat (Journal of Health Science of Thailand, 1994)
During 1989-1993, many estimations and projections have been done. All of these elucidated the progressive epidemic of HIV in the country. It is estimated that number of HIV infected people might increase from 50,000 at the end of 1989 to 700,000 or more in mid 1998. It is projected that there will be many more AIDS patients in the future. Reliablity of estimation and projection analysis depend on assumptions used, analysis methodology and basic information utilized in the calculation. In the case of projection, it has to deal, in addition. with uncertainty of the data that will change with time. Although the methodology for estimation and projection has been developed, there is still lack of representative data. Those who want to cite the result of estimation and projection should be aware of the details of the analysis and it‘s limitation. Since it is for sure that estimation and projection will be done again in the future, process of the estimation and projection for HIV/AIDS should not only be based on reliable technique but should also be cheap and easy to repeat.